Ficcionalización de las experiencias sexuales. El discurso de los usuarios de foros de internet sobre kinesiólogas - Romero Ramirez, Diego Alejandro (2017)
One of the consequences of the vertiginous technological advance of the last years has been the alteration of one of the pillars of the daily life of the human being: sexuality. Thus, the traditional sexual practices acquired new possibilities and scenarios for their development. This panorama, in turn, provided the academics new points of view to approach to this field of study. Therefore, this article analyzed the characteristics of the speech of the users that form part of the peruvian forum ZonaCaleta, virtual space dedicated to the exchange of information on sexual encounters with prostitutes. In order to do that, 100 posts published in 2015 were taken as sample and they were examined through three matrices: the first one searched for linguistic peculiarities in the discourse, the second identified some tensive dynamics that determined the feelings of pleasure or displeasure the forum members felt, and the third analyzed the platform itself. Thanks to these tools, we arrived at some important conclusions such as the existence of a sociolect among the users, the fictionalization of the stories due to the use of literary elements or the marked reification of the female body present in the discourse of the forum members.